Clinical and molecular-genetic markers of ADHD in children - Drtílková, Ivana; Šerý, Omar; Theiner, Pavel; Fiľová, Alena; Žáčková, Markéta; Balaštíková, Blanka; Znojil, Vladimír (Neuro-endocrinology letters, 2008)
OBJECTIVES: The objective was to make a contribution to deepening the knowledge of the etiopathogenesis of ADHD. DESIGN: In an association study design, an analysis of polymorphisms of selected genes was conducted in 119 hyperkinetic boys and a control group of boys, aged 7-13. Furthermore several psychologically determined subgroups were identified. A connection between psychological functions (endophenotypes) and genes were looked for. RESULTS: There was a statistically significant difference found in allelic and genotype frequencies of the TaqI A polymorphism of the DRD2 gene. The frequency of the allele A1 in hyperkinetic boys and the control subjects was 0.26 and 0.15, respectively (p<0.003). A statistically significant occurrence of atypical genotypes (8/10, 7/10 and 10/11) of the DAT1 gene was also found in hyperkinetic boys and a connection between the M235 polymorphism of the angiotensinogene gene and the positive family history of psychiatric illness was found in probands (p=0.031). Significant correlations between the results of some neuropsychological tests and genes for neuro-/immunomodulators (IL-6, TNF-alpha) and the gene for the brain-derived neurotrophic factor (BDNF) were found. CONCLUSION: The study showed a statistically significant prevalence of A1 allele of the DRD gene in the hyperkinetic group. We also found a significantly higher incidence of atypical DAT genotypes in the hyperkinetic group. Furthermore we found significant connections with particular gene polymorphisms which may hypothetically represent a neurodevelopmental risk factor in the etiopathogenesis of the disorder (IL-2, IL-6, TNF-alpha, BDNF). We further found a connection of the M235 polymorphism of the AGT (angiotensinogene) gene to positive family history of psychiatric illness (p=0.031). As for cognitive characteristics, we identified three subtypes with different cognitive performance profiles. This finding shows interindividual variability of cognitive style in the group of hyperkinetic boys.
Keywords: Attention Deficit Disorder with Hyperactivity; Genetic Markers; Receptors, Dopamine D2; Neuropsychological Tests; methylfenidát; Discrimination, Psychological; Humans; Attention; neuropsychologické testy; Genotype; receptory dopaminu D2; Methylphenidate; Czech Republic; Financing, Organized; vnímání tvaru; Phenotype; financování organizované; Form Perception; Polymorphism, Genetic; Psychiatric Status Rating Scales; mužské pohlaví; pozornost; Česká republika; polymorfismus genetický; Psychomotor Performance; diskriminace (psychologie); Adolescent; hyperkinetická porucha; fenotyp; biologické markery; psychiatrické posuzovací škály; genotyp; lidé; mladiství; dítě; genetické markery; Biomarkers; stimulanty centrálního nervového systému; Child; Male; Central Nervous System Stimulants; psychomotorický výkon